A Study of Affixation in Korean Students' Descriptive Composition BIPA Advanced Level - Agus Sulaeman; Kim Dong Hoon (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2026)
This study aims to describe the use of affixation in narrative texts that highlight natural phenomena and the experiences of the speakers in them. Affixation is one of the morphological processes in Indonesian that plays an important role in word formation, word class changes, and the development of meaning in a discourse. This study uses a qualitative approach with a descriptive method. The research data are in the form of linguistic units containing affixation processes found in the text, including prefixes, suffixes, infixes, and confixes. The data collection technique was carried out using the listening and note-taking method through careful reading of the analyzed text. The results of the study show that the analyzed text contains the use of prefixes, suffixes, and confixes, while infixes are not found. The dominant prefixes used include me-, di-, ber-, and ter- which function to form active verbs, passive verbs, and express states and events. Suffixes such as -an, -itas, and -nya play a role in forming concrete and abstract nouns, as well as providing emphasis on meaning in sentences. In addition, the confixes me-kan, me-i, and ke--an are used to form causative meanings, processes, and certain states or situations. The absence of infixes indicates that the text makes greater use of productive and commonly used affixation forms in modern Indonesian.